Can someone check this for me, please.

2. Originally Posted by Alienis Back
Can someone check this for me, please.
Stop at the middle line. The last line is wrong (as you would readily see if you expanded)

3. Why? Isn't the second line a perfect square trinomial?

4. Originally Posted by Alienis Back
Why? Isn't the second line a perfect square trinomial?
I hope that when you expanded $\displaystyle (3a - 3b)^2$ (as I suggested) you got $\displaystyle 9a^2 - 18ab + 9b^2$ ....

This is obviously not the same as $\displaystyle 3a^2 - 4ab + 3b^2$.

5. Originally Posted by Alienis Back
Why? Isn't the second line a perfect square trinomial?
===============================================
Alienis Back,
2nd line is not correct.
see my attachment.

6. Ok. Last line is certainly wrong. No doubt. So, It shouldn't be further factor-able, should it? And where is your attachement, 2976math?

7. simplfy.pdf
Here we go.

8. 2976math, look for the clip.

9. Originally Posted by 2976math
simplfy.pdf
Here we go.
Your answer is useful in that it clearly shows why the trinomial in brackets cannot be factorised (because it's a sum of two squares). But it's not what I'd give as an answer to the original question (I'd stop at the middle line).

10. Originally Posted by Alienis Back
2976math, look for the clip.
Can you see attachment?

11. simplfy.pdf

I did in hurry.
18(a^2)(b^2) should be always there from 3rd line to 5th line.

12. Yep!

2976math, That was quite useful, but is a lot more that I expected. Quite useful but as I see it, it doesn't mean my aproach is wrong. I'll keep on studying yours anyway.

Thanks a lot guys.